Innovative, Modular Building Facades - as a Tool to Counteract the Effects of and to Prevent Climate Change - Kamińska, Patrycja; Michalak, Hanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents original research, encompassing the results of analyses of modular building façade solutions, as well as innovative design concepts based on these results by students of the Faculty of Architecture at the Poznań University of Technology. Adapting architecture to climate change is the main objective behind research and innovative designs.
Keywords: module; prefabrication; ecology; environment; architecture; construction; façade; innovation; aestetics; technology; concept; moduły; prefabrykacja; ekologia; środowisko; architektura; budowa; fasada; innowacja; estetyka; technologia